Perancangan Interior Hotel Bandung Permai di Jember - Chung Sen (Intra, 2016)
Bandung Permai Hotels is one of the most famous hotels in Jember city and have been the most favorite venue for local and foreign tourists. Bandung Permai only had a minor change on its interior design that caused a decreasing values of competitiveness against a thriving hotel in Jember city. This design aims to improve and regain the competitiveness as well as create a new atmosphere in Bandung Permai interior Hotel by combining cultural elements with modern elements, especially in the matters of interior design.